The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/prp2.775
|View full text |Cite
|
Sign up to set email alerts
|

The role of sex, age and genetic polymorphisms of CYP enzymes on the pharmacokinetics of anticholinergic drugs

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 144 publications
(313 reference statements)
0
14
0
Order By: Relevance
“…Regulation of P450 eicosanoid levels is determined by the induction or repression of the cytochrome P450 enzymes responsible for their formation ( Ng et al, 2007 ). According to a previous study, an approximate 3.5% decline in CYP450 content occurs for each decade of life ( Trenaman et al, 2021 ). Therefore, a higher 14,15-DiHETrE level in youth age probably results from higher CYP 450 content at the young.…”
Section: Discussionmentioning
confidence: 93%
“…Regulation of P450 eicosanoid levels is determined by the induction or repression of the cytochrome P450 enzymes responsible for their formation ( Ng et al, 2007 ). According to a previous study, an approximate 3.5% decline in CYP450 content occurs for each decade of life ( Trenaman et al, 2021 ). Therefore, a higher 14,15-DiHETrE level in youth age probably results from higher CYP 450 content at the young.…”
Section: Discussionmentioning
confidence: 93%
“…This may be along with the increase of age, the physiological function and compensatory adaptability of the human body are decreased year by year, and the effects of the body on the clearance rate of liver and kidney drugs are also decreased. Besides, CYP450 changes with age (Trenaman et al ., 2021). However, there is no difference in RIS/9-OH-RIS among people of different ages.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid antidepressant effect of scopolamine was observed in both sexes; however, one study showed the magnitude was higher in women than men, which may be driven by renal elimination rate. Although there are no studies examining pharmacokinetic differences of scopolamine in men versus women, results from drugs with weak anticholinergic activity such as amantadine and digoxin suggest slower clearance in females compared to males, due to sex differences in renal tubule secretion by organic cation transporters [ 106 ]. A second possibility is p-glycoprotein transporter polymorphisms may lead to variability in efficacy [ 76 , 107 ].…”
Section: Discussionmentioning
confidence: 99%